A unique fatal case of Waterhouse–Friderichsen syndrome caused by Proteus mirabilis in an immunocompetent subject: Case report and literature analysis. Issue 34 (August 2019) - Ventura Spagnolo, Elvira; Mondello, Cristina; Roccuzzo, Salvatore; Stassi, Chiara; Cardia, Luigi; Grieco, Angela; Raffino, Cataldo
Abstract: Introduction: The Waterhouse–Friderichsen syndrome (WFS), also known as purpura fulminans, is a potentially lethal condition described as acute hemorrhagic necrosis of the adrenal glands. It is often caused by infection. Classically, Neisseriae meningitidis represents the main microorganism related to WFS, although, infrequently, also other infectious agents are reported as a possible etiologic agent. The authors report the first case of death due to Proteus mirabilis infection, with postmortem evidence of WFS. Patient concerns: After a facial trauma that provoked a wound on the nose, the subject, a healthy 40-years old man, was conducted to the local hospital (in Sicily, Italy) after the primary care he was discharged. Subsequently, after 2 days of general malaise, he returned to the hospital due to the worsening of the clinical condition. During the hospitalization, hypotension, and neurological impairment appeared; the laboratory analysis showed leukocytosis and the alteration of renal, hepatic and coagulative parameters. Microbiological blood analysis resulted positive for a P mirabilis infection. Diagnosis: Multiorgan failure (MOF) with disseminated intravascular coagulation (DIC) due to sepsis was diagnosed. Interventions: The practitioners administered intensive support, antibiotic therapy, antithrombin III, vitamin K, and plasma. Outcomes: After 3 days the subject died. The autopsy and the microscopic investigation were performed revealing, also, the adrenal diffuse micronodular hyperplasia associated with a cortico-medullary hemorrhagic apoplexy. Conclusion: To our knowledge, this is the first case of MOF with WFS due to P mirabilis infection. This case report suggests that P mirabilis should be added to the list of unusual bacteria causing WFS. Furthermore, it supports the theory that any bacterium which causes DIC may cause adrenal hemorrhage and should suggest to clinicians the importance to consider a potential adrenal involvement in every patient with sepsis and DIC.